The Role of TBNA in Diagnosis and Treatment of Lung Diseases - Mengzhao WANG; Xiao ZHAO (Chinese Journal of Lung Cancer, 2010)
In the last 30 years, clinical application of transbronchial needle aspiration (TBNA) has proved its efficiency, accuracy, safety and cost-effectiveness, particularly in diagnosing and staging lung cancer as well as in diagnosing benign diseases. The application of endobronchial ultrasound (EBUS) increased the accuracy of TBNA. Endobronchial ultrasound guided transbronchial needle aspiration (EBUS-TBNA) has superior performance and allowing real-time sampling under direct vision. Combination of EUBS-TBNA and traditional methods (CT, PET, mediastinoscopy, et al) can improve the diagnostic rate and negative predictive value. In the future, EUBS-TBNA may have applications in both benign and malignant lung diseases as a routine examination.